Daily Medical Liaison Is Associated with Reduced Length of Stay and Complications in Selected Patients Admitted to a Regional Vascular Surgery Service - Mitchell, Emma (Geriatrics (Basel), 2020)
Older adults undergoing vascular surgery are particularly vulnerable to adverse outcomes by virtue of their vascular risk factors and medical comorbidities. This study aimed to determine the impact of daily medical liaison for patients aged 65 years and older admitted to a regional vascular surgery centre. This was a descriptive before-and-after study concerning 375 patients. The primary outcome measure was length of stay (LOS). Following intervention, we identified a reduction in mean LOS in the sample from 10.75 to 7.95 days (p = 0.635, 95% Confidence Interval [CI] 0–5 days) with a statistically significant reduction in mean LOS for “stranded” patients admitted for more than seven days (mean 7.84 days reduction, p = 0.025, 95% CI for mean difference, 1.5 to 14 days). These patients did not display elevated 30-day readmission rates (12/60 to 8/72, p = 0.156, 95% CI −3% to 21%). A non-significant reduction in postoperative complications was seen in all patients in the post-intervention cohort (1.09 to 0.86 per person, p = 0.181, 95% CI −0.11 to 0.56), reaching statistical significance in emergency vascular admissions (1.81 to 0.97 complications per person, p = 0.01, mean difference = 0.84, 95% CI 0.21–1.46). This study demonstrated reduced LOS and complications in selected older patients admitted under vascular surgery after the introduction of a daily medical liaison model. These data are amongst the first to reproduce randomised controlled trial findings in a non-trial setting. Subgroup analysis indicates that patients admitted with acute pathology and those with long LOS may benefit most from medical liaison where resources are finite.